2024
DOI: 10.1038/s41564-024-01628-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevotella copri and microbiota members mediate the beneficial effects of a therapeutic food for malnutrition

Hao-Wei Chang,
Evan M. Lee,
Yi Wang
et al.

Abstract: Microbiota-directed complementary food (MDCF) formulations have been designed to repair the gut communities of malnourished children. A randomized controlled trial demonstrated that one formulation, MDCF-2, improved weight gain in malnourished Bangladeshi children compared to a more calorically dense standard nutritional intervention. Metagenome-assembled genomes from study participants revealed a correlation between ponderal growth and expression of MDCF-2 glycan utilization pathways by Prevotella copri strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…We performed a marker gene-based phylogenetic analysis to more precisely contextualize the relationship between these two Prevotella sp900557255 MAGs that either exhibited a positive relationship with WLZ in both the SAM and MAM phases (BgpSM0038) or only during the MAM phase (BgpSM0080). The analysis included (i) all Prevotella MAGs identified in this study regardless of their WLZ association, (ii) the 11 P. copri MAGs identified in our prior primary MAM study, including the two that were significantly positively associated with WLZ (Bg0018 and Bg0019) ( 9 ), (iii) P. copri strains (Bg131, BgF5_2 and BgD5_2) cultured from Bangladeshi children living in Mirpur that we have shown to be key mediators of MDCF-2 glycan metabolism and key effectors of fatty acid and amino acid metabolism in the intestinal epithelium of gnotobiotic mice ( 10 ), and (iv) publicly-available reference genomes representing a diversity of clade-level P. copri designations and related Prevotella species (Publicly available cultured P. copri isolates and MAGs have been taxonomically assigned clades designated A-D) ( 28 ). The results revealed that the positively WLZ-associated Prevotella sp900557255 MAGs identified in the current study belong to a branch of P. copri clade ‘A’ that also contains the WLZ-associated P. copri MAGs identified in the prior primary MAM RCT ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We performed a marker gene-based phylogenetic analysis to more precisely contextualize the relationship between these two Prevotella sp900557255 MAGs that either exhibited a positive relationship with WLZ in both the SAM and MAM phases (BgpSM0038) or only during the MAM phase (BgpSM0080). The analysis included (i) all Prevotella MAGs identified in this study regardless of their WLZ association, (ii) the 11 P. copri MAGs identified in our prior primary MAM study, including the two that were significantly positively associated with WLZ (Bg0018 and Bg0019) ( 9 ), (iii) P. copri strains (Bg131, BgF5_2 and BgD5_2) cultured from Bangladeshi children living in Mirpur that we have shown to be key mediators of MDCF-2 glycan metabolism and key effectors of fatty acid and amino acid metabolism in the intestinal epithelium of gnotobiotic mice ( 10 ), and (iv) publicly-available reference genomes representing a diversity of clade-level P. copri designations and related Prevotella species (Publicly available cultured P. copri isolates and MAGs have been taxonomically assigned clades designated A-D) ( 28 ). The results revealed that the positively WLZ-associated Prevotella sp900557255 MAGs identified in the current study belong to a branch of P. copri clade ‘A’ that also contains the WLZ-associated P. copri MAGs identified in the prior primary MAM RCT ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The underlying strain specificity is remarkable; the two WLZ-associated P. copri MAGs in this study and the two identified in the previous study are phylogenetically closely related members of P. copri clade A; they are distinguishable from the non-WLZ associated clade A P. copri MAGs present in the gut (fecal) microbial communities of study participants based on their content of PULs known or predicted to target glycans present in MDCF-2. These observations, combined with the results of (i) our growth assays of cultured Bangladeshi P. copri strains, whose repertoires of PULs correspond to those in the MAGs, in defined media supplemented with glycan structures present in MDCF-2 ( 9 ) and (ii) our ‘reverse translation’ studies in gnotobiotic mice demonstrating the importance of cultured Bangladeshi P. copri strains embodying these genomic features in mediating MDCF-2 glycan utilization, energy metabolism in gut epithelial cells, and weight gain ( 10 ), provide an expanding body of evidence that P. copri functions at the intersection between MDCF-2 metabolism and rescue of growth faltering in Bangladeshi children with MAM. The genomic features that distinguish these growth-promoting strains (MAGs) (notably PULs) provide a way for characterizing their distribution in human populations, including women and children living in different low- and middle-income countries where the burden of undernutrition is great.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation